Effect of Moringa Leaf Infusion (Moringa oleifera) on Reducing Blood Glucose and Total Cholesterol Levels in Mice (Mus musculus) with Diabetic Ulcers - Napitupulu, Helen Debora; Siahaan, Jekson Martiar; Simangunsong, Batara (Indonesian Journal of Medicine, 2024)
Background: Diabetes mellitus is a chronic disease in the form of metabolic disorders, which is characterized by blood glucose levels (KGD) that exceed normal limits and are accompanied by impaired metabolism of carbohydrates, lipids, and proteins, as a result of abnormalities in insulin secretion. Diabetics are known to have slow wound healing. Moringa oleifera leaves or moringa plants contain flavonoid compounds, which can decrease glucose absorption. This study aims to determine the effect of moringa leaf infusion on blood sugar levels, glucose tolerance, cholesterol levels, body weight, and wound healing speed in mouse model animals. Subject and Method: This study is experimental using a posttest only controlled group design, using 25 male mice (Mus musculus) divided into 5 groups. The study was conducted at the Phytochemistry and Animal House Laboratory, Faculty of Medicine, Methodist University Indonesia from March to May 2022. The bound variables were body weight measured using a scale, current blood glucose levels and blood glucose levels with glucose loading measured with strips and glucometers, total cholesterol levels measured using strips and cholesterol measuring devices, and the length of mice wounds measured using a ruler. The free variable is the variation in the dose of moringa leaf infusion. The data were analyzed using the Anova and Kruskal-Wallis tests. Results: The administration of moringa leaf infusion had a significant effect on the reduction of the levels of each variable, namely a dose of 10% in body weight, a dose of 30% in KGD, 20% in KGD with glucose loading, 20% in cholesterol, and 20% in wound closure, which was proven based on the results of statistical tests. Conclusion: Moringa leaf infusion can lower blood sugar levels, blood sugar levels by glucose depletion, cholesterol levels, body weight, and accelerate wound healing in sucrose-induced mice, high fat diet, and PTU.